Cognitive strategies and reading comprehension in students of basic and higher level - Yana, Marisol (2019)
The research focused on assessing the level of scientific evidence that exists about the use of cognitive strategies as a determinant in the reading comprehension activity in students of different educational levels: primary, secondary and higher. A systematic review of scientific articles and theses was carried out, without restriction of dates or types of study. We reviewed the full articles that included on the importance of cognitive strategies and reading comprehension. Ten articles were selected, most of these looking for the relationship exists. Good percentage of the authors of the articles and thesis reviewed conclude that the good use of cognitive strategies develops reading comprehension skills reaching the desired goal, the understanding of the text. It even depends on these strategies that the student develops increasingly complex performance criteria for reading comprehension.